Enzymatic activity of sod-podzolic soils under the conditions of exposure to emissions of a building materials manufacturing enterprise - Samusik, Elena A.; Golovatyi, Sergey E. (Journal of the Belarusian State University. Ecology, 2022)
The article presents the results of studies of the influence of a large industrial enterprise on the soil cover. It is shown that the enterprise for the production of building materials significantly affects the agrochemical and biological indicators of soils. This is manifested primarily in the change in the acidity of soddy-podzolic sandy loamy soils and the shift in the pHKCl index towards alkalization. It has been established that soils with slightly alkaline (pHKCl from 7.06 to 7.42) and alkaline environmental conditions (pHKCl from 7.55 to 8.09) prevail in this zone. The features of the course of enzymatic processes in soils subject to gas and dust pollution have been established. The levels of activity of redox (catalase, dehydrogenase) and hydrolytic (invertase, urease) enzymes were determined in the distance gradient from the source of pollution and along the directions of air mass propagation. There is a decrease in the activity of these enzymes in soddy-podzolic sandy loamy soils of forest and agricultural lands as one approaches the source of pollution. It is shown that within a radius of up to 2 km from the source of pollution, the soils of forest and agricultural lands are characterized as very poor in terms of enrichment with the studied enzymes. According to the results of the correlation analysis, there is a change in the influence of the reaction of the soil environment on the studied enzymes with a statistically significant negative relationship.